COMPARITIVE STUDY OF LABOR LAW: THE METHODOLOGICAL IMPORTANCE - Вишновецька, Світлана Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article an author researches the methodological importance of comparative study in the labour relations law field and stadies the problems of comparative-legal analysis.